Investigation on Losses Connected with Steam Condensation in Turbine Cascades - Stastny, Miroslav (New Ideas Concerning Science and Technology Vol. 4, 2021)
The process of condensation of the steam flowing through the LP part of a turbine is evidently the last mystery of steam turbines. The mathematical approach used for the condensation of flowing steam is based on the homogeneous condensation and on the binary nucleation of water droplets with a representative chemical impurity NaCl. The physical and mathematical models are briefly described. The homogeneous and binary nucleation numerical models are then used for the calculation of steam flow with condensation in the 2D nozzle-blade cascades of the first wet stage of the low-pressure part of a fossil-fuel condensing steam turbine and of a similar cascade of the LP part of a nuclear turbine. Main results of the calculations are presented and analyzed. It was used humid air for experimental investigation some phenomena of the two-phase flow, e. g. modelling water steam condensation in the flow in LP nozzle cascade of a steam turbine. Condensation effects in transonic flow in experimental nozzle cascade validated the losses. With the effects of steam chemistry on the surfaces of turbine blades in the transition zone of the LP part of a steam turbine are connected further losses.